2012
DOI: 10.1002/pi.4440
|View full text |Cite
|
Sign up to set email alerts
|

Facile and efficient synthesis of hyperbranched polyesters based on renewable castor oil

Abstract: Hyperbranched polyesters with thioether linkages were facilely prepared from methyl 10-undecenoate, a castor oil-derived renewable chemical. The monomer was obtained in excellent yield through thiol-ene click chemistry in the presence of catalytic amounts of photoinitiator under UV irradiation. Subsequent bulk polycondensation via a transesterification process catalyzed by Ti(OBu) 4 , Sb 2 O 3 or Zn(OAc) 2 gave hyperbranched polyesters with high molecular weights and unusual crystalline properties. The degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
1
22
0
3
Order By: Relevance
“…Recently, Li and coworkers also reported T2 addition to methyl 10-undecenoate benefiting from click chemistry feature of DMPA-photoinitiated thiol-ene reaction. 33 In this case, large-scale reaction with yields up to 95% in less than 10 min without any stirring were reported compared with the low monomer preparation efficiency reported by T€ ur€ unc¸and Meier (66% yield at 35 C and 1500 rpm for 6 days at 50 mmol scale). Indeed, the authors reported the self-polycondensation of M7 under various reaction conditions producing high-molecular-weight hyperbranched polyesters with unusual crystalline properties.…”
mentioning
confidence: 89%
“…Recently, Li and coworkers also reported T2 addition to methyl 10-undecenoate benefiting from click chemistry feature of DMPA-photoinitiated thiol-ene reaction. 33 In this case, large-scale reaction with yields up to 95% in less than 10 min without any stirring were reported compared with the low monomer preparation efficiency reported by T€ ur€ unc¸and Meier (66% yield at 35 C and 1500 rpm for 6 days at 50 mmol scale). Indeed, the authors reported the self-polycondensation of M7 under various reaction conditions producing high-molecular-weight hyperbranched polyesters with unusual crystalline properties.…”
mentioning
confidence: 89%
“…Gleichfalls wurde 17 b als Startmaterial in einer Reaktion mit Thioglycerin verwendet, [128e, 161] was zu Polyestern mit einem hohen Grad an Verzweigung und mit niedriger inhärenter Viskosität führte. [161] AB 2 -und AB 3 -Monomere für hochverzweigte Polyester wurden ebenfalls über Epoxidierung und Ringçffnung von 2 b, 6 b, 7 b und 17 b erhalten. [162] Interessanterweise war der Grad der Verzweigung sowohl vom Typ des Monomers als auch vom Umsatz und dem eingesetzten Katalysator abhängig.…”
Section: Hochverzweigte Polymereunclassified
“…29 and Li and coll. 30 have already used this strategy for a AB2-type monomer synthesis from thioglycerol and methyl undecenoate that was used in selfpolycondensation to give linear or hyperbranched polymers. Lastly, the tetraol carbonation was performed in DMC as reactive solvent using K2CO3 as catalyst.…”
Section: Cyclic Carbonate Synthesismentioning
confidence: 99%